2017
DOI: 10.1097/j.pain.0000000000000977
|View full text |Cite
|
Sign up to set email alerts
|

Placebo effects of a sham opioid solution: a randomized controlled study in patients with chronic low back pain

Abstract: This study tested the experimental placebo effect in a group of chronic pain patients. Forty-eight patients having chronic back pain participated in a randomized clinical trial that tested the efficacy of a sham opioid solution (NaCl) compared with an alleged neutral, completely inactive solution (NaCl). We shaped the placebo effect by 2 interventions: verbal instruction and conditioning. The patients were either told that the "solution reduces pain and improves physical capacity" or the "solution is neutral, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
63
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 55 publications
(70 citation statements)
references
References 34 publications
1
63
0
2
Order By: Relevance
“…Laboratory studies showed that patients with chronic Irritable Bowel Syndrome (Kaptchuk et al, 2008; Vase, Robinson, Verne, & Price, 2003, 2005), idiopathic and neuropathic pain (Petersen et al, 2014, 2012; Vase, Petersen, & Lund, 2014), and low back pain (Carvalho et al, 2016; Hashmi et al, 2012; Klinger, Kothe, Schmitz, Kamping, & Flor, 2017), show robust placebo hypoalgesic responses.…”
Section: Clinical Application Of Analgesic Placebos: Ethical Tenablementioning
confidence: 99%
See 2 more Smart Citations
“…Laboratory studies showed that patients with chronic Irritable Bowel Syndrome (Kaptchuk et al, 2008; Vase, Robinson, Verne, & Price, 2003, 2005), idiopathic and neuropathic pain (Petersen et al, 2014, 2012; Vase, Petersen, & Lund, 2014), and low back pain (Carvalho et al, 2016; Hashmi et al, 2012; Klinger, Kothe, Schmitz, Kamping, & Flor, 2017), show robust placebo hypoalgesic responses.…”
Section: Clinical Application Of Analgesic Placebos: Ethical Tenablementioning
confidence: 99%
“…Moreover, analgesic placebos can lead to excellent clinical results for patients with chronic pain (Carvalho et al, 2016; Klinger et al, 2017), idiopathic and neuropathic pain (Petersen et al, 2014, 2012; Vase et al, 2014), migraine (Kam-Hansen et al, 2014), and knee osteoarthritis (Gollub et al, 2018; Tetreault et al, 2016). Therefore, why should analgesic placebos not be used in daily clinical practice?…”
Section: Clinical Application Of Analgesic Placebos: Ethical Tenablementioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, some learning processes may occur independently of conditioning by means of vicarious observation, social learning, or verbal communication (Kirsch 1985, 1997, 2004). Given that placebo effects have been demonstrated to be influenced by verbal suggestions, conditioning processes, social observation, personality factors, and genetics, the underlying endogenous mechanisms mediating the processing of the vast amount of information within a clinical environment are far more integrated and complex than one single process alone (Bartels et al 2014; Benedetti et al 2003; Brody and Brody 2000; Colagiuri et al 2015; Colloca and Benedetti 2006, 2009; Colloca and Grillon 2014; Corsi and Colloca 2017; Darragh et al 2015; Hall, Loscalzo, and Kaptchuk 2015; Kirsch 2004; Klinger et al 2017b; van Laarhoven et al 2011; Vase et al 2003; Vogtle, Barke, and Kroner-Herwig 2013; Wang et al. 2017).…”
Section: The Conditioning Response Theorymentioning
confidence: 99%
“…via instructions) and reinforced expectations (e.g. via exposure to a pain reduction using a behavioral conditioning manipulation) would affect not only the perception of experimental acute pain intensity but also pre-existing clinical pain, as well as back pain-related behaviors and functional capacity in patients with history of chronic back pain [9]. An inactive solution (NaCl) was presented as an effective treatment (sham “opioid” solution) to chronic back pain patients.…”
mentioning
confidence: 99%